Breast cancer and dietary patterns: a systematic review. (13th December 2013) - Albuquerque, Rita CR; Baltar, Valéria T; Marchioni, Dirce ML
<x xml:space="preserve">Abstract</x> This systematic review collates research on the topic of dietary patterns and breast cancer risks. The literature search targeted epidemiological studies published up to December 2012 and was conducted using the Medline (U.S. National Library of Medicine, Bethesda MD, USA) and Lilacs (Latin American and Caribbean Health Sciences, São Paulo, Brazil) databases. The following search terms were used: breast cancer, breast neoplasm, breast carcinoma, diet, food, eating habits, dietary patterns, factor analysis, and principal component analysis. Only studies that used factor analysis techniques and/or principal component analysis were eligible, and a total of 26 studies were included. The findings of these studies suggest the Mediterranean dietary pattern and diets composed largely of vegetables, fruit, fish, and soy are associated with a decreased risk of breast cancer. There was no evidence of an association between traditional dietary patterns and risk of breast cancer, and only one study showed a significant increase in risk associated with the Western dietary pattern. Diets that include alcoholic beverages may be associated with increased risk.